Implementasi Konsep Pemikiran Etika Ibnu Miskawaih - Achmad Khudori Soleh; Hasan Assidiqi, Ali (Al Hikmah: Jurnal Studi Keislaman, 2023)
Abstract People should have good ethics and morals. However, in the modern era, morality towards God and man began to decline. This is evidenced by the many viral news and people's daily lives that have deviated. They feel that they are far away and cannot be changed because it has become who they are. The purpose of this paper is to illustrate how to behave toward God and man without exaggeration so that good is more apparent than bad. The research method used is literature study, with historical-critical-philosophical approach and descriptive-analytical analysis. The results were that 1) Ibn Miskawaih's ethical thinking was built on his view of the human soul. Where man first knows his soul by cleansing from heart disease and excessive love for the world. Heart disease and soul cleansing can be done by always learning a lot to do good, staying away from greedy friends, living in simple circumstances even though it has advantages, preparing to fight lust, learning about religion, and introspection. 2) The importance of the middle position as a guide in the point of goodness according to Ibn Miskawaih is important. Where one must not be extreme deficient or extreme excessive. It must be a middle extreme or middle position which is said to be the true good and must be used as the foundation of the individual. 3) Implementation can be done by cleansing the heart, then getting used to doing good so that later it becomes a habit that leads to divine health. The culmination of Ibn Miskawaih's ethical thought from the above is being able to do good directly without thinking because it has become a habit to do good. Keywords: Ethics, Ibn Miskawaih, and Implementation.